2008
DOI: 10.1152/japplphysiol.01204.2007
|View full text |Cite
|
Sign up to set email alerts
|

MRI analysis of structural changes in skeletal muscles and surrounding tissues following long-term walking exercise with training equipment

Abstract: Muscular recovery after exercise is an important topic in sports medicine, and accurate and quantitative measurements of changes in muscle are required to assess muscular recovery. In the present study, we report a new analytical method to measure muscular changes quantitatively. The technique consists of three independent methods: image processing of two-dimensional MR images, morphological analysis using three-dimensional MR images, and diffusion tensor MRI. Using this method, we investigated changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…[7][8][9]11 Moreover, it is clear that muscle morphology changes by various resistance training. 13,14 Thus, the maximal CSA location of each RC muscle may change as a physical adaptation to the repetitive sports activities, although we did not clearlyˆnd such changes. Future study should evaluate the data of various athletes, especially baseball pitchers, who are subject to shoulder injuries, 15 to further clarify the morphological characteristics of the athlete's shoulder.…”
Section: Discussionmentioning
confidence: 85%
“…[7][8][9]11 Moreover, it is clear that muscle morphology changes by various resistance training. 13,14 Thus, the maximal CSA location of each RC muscle may change as a physical adaptation to the repetitive sports activities, although we did not clearlyˆnd such changes. Future study should evaluate the data of various athletes, especially baseball pitchers, who are subject to shoulder injuries, 15 to further clarify the morphological characteristics of the athlete's shoulder.…”
Section: Discussionmentioning
confidence: 85%
“…Previous research established DTI as a reproducible and valid technique (23,24,26) to evaluate muscle status (10,11,(27)(28)(29). We extended the clinical applicability of this technique by developing a protocol that covers both upper legs from hip to knee in one examination.…”
Section: Resultsmentioning
confidence: 99%
“…29, 63, 7779 In 2006, Martel et al reported that nine weeks of heavy-resistance training of the quadriceps resulted in an increase in Type II fiber cross-sectional area in healthy, older adults. 78 In 2008, Suetta and colleagues reported that 12 weeks of resistance training of 60 to 86 year-old individuals post unilateral hip arthroplasty resulted in Type I and Type II fiber area increases, increases of 29 to 30% in dynamic muscle strength, and improved stair climbing power.…”
Section: Interventionmentioning
confidence: 99%